THE SIMILARITIES AND DIFFERENCES BETWEEN THE STRATEGIES OF ENGLISH-INDONESIAN TRANSLATION OF ENGLISH PARTICIPIAL CLAUSES IN SIDNEY SHELDONâS MORNING, NOON AND NIGHT AND JOHN GRISHAMâS THE STREET LAWYER - Winiharti, Menik (Universitas Muhammadiyah Surakarta, 2011)
The participial construction is one that exists in English but not in Indonesian.Â With regard to the translation, it might not be easy to translate a text having aÂ structure that exists in one language (as a source language/SL) but not in the otherÂ (as a target language/TL). This study analyses the English participial clauses andÂ their Indonesian translations in terms of the strategies applied in the translation. ItÂ focuses on two types of participial clauses; they are adverbial clauses and adjectival clauses. The data evaluated are the texts in Sidney Sheldonâs novel Morning,Â Noon, and Night (1995) which is translated into Pagi, Siang dan Malam (1996) byÂ Hendarto Setiadi and John Grishamâs novel The Street Lawyer (1998) which isÂ translated into Pengacara Jalanan (1998) by Widya Kirana and Diniarty Pandia.Â This study compares the strategies that the translators apply and tries to find theÂ similarities as well as differences in the strategies used in the translations of theÂ two novels. To reach these objectives, the English version and the Indonesian translations are compared and analyzed to determine the strategies applied and to findÂ the similarities and differences of the strategies.Keywords: participial clauses, translation, strategies, Source Language (SL), Target Language (TL), adverbial clauses, adjectival clauses